Immune modulation of Prevotella intermedia colonization in squirrel monkeys. - Clark, W B (1991)
Colonization of the gingival crevice by black-pigmented Porphyromonas or Prevotella spp. (BP/P), including Porphyromonas gingivalis (formerly Bacteroides gingivalis) and Prevotella intermedia (formerly Bacteroides intermedius), is thought to be an important ecological event which may result in the destruction of connective tissues supporting the teeth. Theoretically, periodontal diseases could be prevented if these or other periodontal pathogenic microorganisms did not colonize the subgingival area. The humoral immune response is one mechanism which may modulate bacterial colonization in the gingival crevice. In the present study, we tested the effect of systemic humoral immunity on subgingival colonization by indigenous P. intermedia in squirrel monkeys (Saimiri sciureus). Animals rendered essentially free of detectable BP/P by a single scaling, 10 days of tetracycline therapy, and toothbrushing three times per week were immunized with P. intermedia 1447 or were sham immunized with phosphate-buffered saline. Subsequently, all oral hygiene procedures were discontinued and five teeth in one quadrant were ligated with bacterium-soaked suture material to facilitate BP/P colonization. Immunization resulted in a significant increase in the level of immunoglobulin G anti-P. intermedia antibody in serum. Two weeks after ligation was initiated, P. intermedia could be detected in five of six sham-immunized and three of six immunized animals. Immunization was associated with a reduction in the emergence of indigenous P. intermedia in the gingival crevice.